Pattern reversal evoked visual potential in the diagnosis of multiple sclerosis. - Matthews, W B (1977)
The pattern reversal evoked visual potential (VEP) was recorded in 37 normal subjects and in 186 patients in whom a diagnosis of multiple sclerosis (MS) was established or suspected. Taking the upper limit of normal as the mean +2.5 SD (111 ms), prolonged latency was found in 75% of definite cases of MS, 58% of probable cases, and 38% of possible cases. A smaller number of patients without prolonged latency had abnormal asymmetry of latency or low amplitude potentials. In patients with a single acute episode of neurological disease resembling MS the incidence of abnormal VEP was very low. In patients examined within three months of an episode of retrobulbar neuritis (RBN), latency was prolonged in 81% of affected eyes, a similar proportion being found in patients with a more remote history of RBN. The importance of establishing the normal for every laboratory engaged on this investigation is emphasised. Prolonged latency of the VEP is common in established MS but has not yet been shown to be a sensitive diagnostic test of the early case.